Integrasi Nilai-Nilai Karakter dalam Pembelajaran di Sekolah Dasar - Ramadhan, Mas Agus Abdul Rahman; Sari, Aldsy Pujita; Oktarina, Yeni; Saputra, Yayan; Maghfira, Saamiyatul (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to describe how elementary school teachers integrate character values ​​in the learning process. The approach used is qualitative with a case study method. The subjects of the study consisted of five class teachers in two public elementary schools in city X who were selected purposively. Data were collected through classroom observations, in-depth interviews, and documentation of lesson implementation plans (RPP). The results of the study indicate that teachers integrate character values ​​such as discipline, responsibility, honesty, cooperation, and tolerance through various strategies, such as role models, verbal reinforcement, value discussions, and contextual approaches in subject matter. However, the implementation of character value integration still faces several challenges, including time constraints, teacher administrative burdens, and lack of training related to character education. This study is that the integration of character values ​​can be carried out effectively if supported by careful planning, teacher commitment, and a conducive school environment.